Does spatial visualization ability improve after studying technical drawing? - Prieto, Gerardo; Velasco, Angela D. [UNESP] (Springer Nature, 2010)
Two studies were carried out to analyze whether learning technical drawing improves a person's ability for spatial visualization. Visualization and inductive reasoning tests were applied at the beginning and end of a course in technical drawing in samples of first year engineering students. In both studies it was observed that a moderate percentage of students improved their Visualization test execution. The improvement was similar in men and women. There was no improvement on the inductive reasoning test. The results support the conclusion that the spatial visualization ability can be improved with training. © 2009 Springer Science+Business Media B.V.
Keywords: Inductive reasoning; Rasch model; Spatial ability; Spatial visualization; Technical drawing; Training